Development of a radial-flow multiple magnetically coupled fan system with one piezoelectric actuator. (October 2017) - Ma, H.K.; Liao, S.K.; Hsieh, C.H.
Abstract: In recent years, piezoelectric fans and their feasibility for use in cooling electronic devices have been widely studied. However, there are few studies that address using a single piezoelectric actuator to generate radial air flow. In this study, a radial-flow multiple fan system (RMFS) was developed for the thermal management of high power LEDs. This system only used one piezoelectric actuator and a magnetic repulsive force to activate up to 20 fans, which featured low power consumption and a large cooling area. The RMFS was mounted in a circular heat sink to evaluate its thermal performance. To find the optimal design for the RMFS, the influence of some geometric parameters was investigated. The performance of different designs was compared with a commercially available axial fan. The results showed that design E had the best thermal performance among the designs because of its relatively large frequency and amplitude. The thermal resistance and percentage improvement under a 35 W heat flux were 0.86 K/W and 36.9%, respectively. In addition, a coefficient of performance (COP) was defined. The COP of design E was approximately 3.7 times that of the rotary fan. For the power consumption aspect, the RMFS is more efficient than the rotary fan.